Pemberian Remisi Kepada Justice Collaborator Dalam Tindak Pidana Korupsi Dihubungkan Dengan Peraturan Pemerintah Nomor 99 Tahun 2012 Tentang Syarat Dan Tata Cara Pelaksanaan Hak Warga Binaan Lembaga Pemasyarakatan - Rifki Zaenal Muhsinin (CV. ITTC INDONESIA, 2024)
Remission to justice collaborators has not been running properly because the requirements and procedures for applying to become a justice collaborator are very difficult, not all perpetrators can become justice collaborators. In 2013-2014, correctional inmates could still get remission, while according to PP 99 of 2012 there are special requirements to get remission. Remission to Justice collaborators Still contains a lot of very strong political nuances from various ethical circles so that this makes it difficult for law enforcement officers to uncover criminal cases.